The Implementation of Group Working in Teaching Reading Narrative Text for Nine Graders of SMP Negeri 50 Surabaya (RETAIN, 2014)
The Implementation of Group Working in Teaching Reading Narrative Text for Nine Graders of SMP Negeri 50 Surabaya Titis Ariwangi English Department, Faculty of Language and Arts, State University of Surabaya Email: lollyboob69@gmail.com Dosen Pembimbing: Rahayu Kuswardani, S. Pd., M.Appl English Department, Faculty of Language and Arts, State University of Surabaya Abstrak Ada empat keterampilan yang termasuk didalam bahasa Inggris, seperti menulis, mendengar, berbicara, dan juga membaca. Melalui membaca, siswa bisa mendapatkan lebih banyak informasi yang mereka butuhkan selama hidup mereka. Ada begitu banyak metode yang dapat digunakan untuk guru mengajar membaca dan juga untuk membantu siswa meningkatkan kemampuan membaca mereka, seperti menggunakan peta konsep dengan kerja kelompok. Penelitian ini adalah deskriptif kualitatif dan tujuan penelitian untuk mengetahui bagaimana pengaplikasian kerja kelompok dengan menggunakan metode peta konsep dalam membaca teks naratif, untuk mengetahui respon siswa terhadap pengaplikasian kerja kelompok dengan menggunakan metode peta konsep, serta respon siswa terhadap kerja kelompok. Subjek penelitian ini adalah siswa kelas sembilan dari SMPN 50 Surabaya yang terdiri 37 siswa IX-C. Subjek diambil berdasarkan nilai rata-rata tertinggi diantara kelas 9A-C sesuai dengan yang disarankan oleh guru bahasa Inggris. Untuk instrumen penelitian, peneliti menggunakan, observasi checklist, catatan dilapangan dan kuesioner . Peneliti menemukan bahwa peta konsep dengan kerja kelompok cukup mudah untuk meningkatkan kemampuan siswa dalam keterampilan membaca. Mengajarkan membaca dengan kerja kelompok menggunakan metode peta konsep menjadi metode baru untuk siswa selama pertemuan. Para siswa mengatakan metode ini lebih baik daripada metode biasa yang mereka gunakan di kelas. Ini akan membantu baik guru dan siswa untuk membuat segala jenis teks lebih mudah untuk dipahami. Kata kunci: Peta Konsep, kerja kelompok, membaca, teks naratif. Abstract There are four skills that are included in English language, such as writing, listening, speaking, and reading. Through reading, students can get more information that they need during their lives. There are so many methods that can be used for teachers to teach reading and also to help the students improve their reading skills, such as using mind mapping with group working. This study is qualitative descriptive research, the purposes of the research are to find out how the application of mind mapping with group working in reading narrative text, to determine students' response toward mind mapping with group working, and also the students' response toward group working. The subjects were ninth grade students of SMPN 50 Surabaya which consists of 37 IX-C students. Subject taken based on the highest average score among the class of 9A-C in that suggested by the English teacher. For the research instrument, the researcher uses, observation checklists, field notes and questionnaires. Researcher found that mind mapping with group working fairly easy to improve students' ability in reading skills. Teach reading by using mind mapping with group working into a new method for students during the meeting. The students said that this method is better than the usual method that they use in the classroom. It will help both teachers and students to make any kind of text easier to understand. Keywords: Concept Maps, group work, reading, narrative text. INTRODUCTION Nowadays, because learning English is an important thing to do, as a language which is used in so many countries, English has become a main language that one must be able to speak with when he/she is applying for a job. In addition, students are required to be able to absorb the information wherever and whenever they are by using English as their language of information. In the process of getting this information, students should have a good capability in reading a text. Nunan (2003: 69) stated that as a second language, reading as an essential skill has to be mastered by students in order to ensure success not only in learning English, but also in any content class. So, having a good skill in reading is a must for students. Spalding (1990: 121-122) stated that reading is one skill that integrates another skill. Hirasawa and Markstein (1983:9) said that reading skill can develop other skills because the students will learn much to comprehend the materials. It can be used to improve student’s ability in listening, reading, writing, and also improved other aspects of language such as vocabulary, grammar, and tenses. Through reading, students can find so much information from book or newspaper or any material that they can read. While they read something, they not just read but also think about what does the writer means. About what kind of tenses that the writer used and what kind of text it is. Maybe people thought that reading in English is the same as reading in their mother language. That is totally wrong; there are so many differences in it (Kustaryo, 1988: 1). The teacher must know how to help the students understand the written texts in easily and properly way. Based on that idea, the study is to suggest teaching reading by using mind mapping with group working method to help students of Junior High School to read and understand written texts easily and properly. Mind mapping is a mind map, or spidergram, is a method for making notes on a topic, prior to writing. This teaching method is chosen because the teacher is adopting reading stages as the strategy to teach reading. In teaching reading, there are three stages that teacher can use to help the students understand more about reading. These three stages are important when teaching a certain reading text. Teachers can adopt these three stages also to know about the implementation of this strategy in teaching narrative text and to know about the students’ ability in reading. The three stages are pre-reading stage, whilst-reading stage, and post-reading stage (Azies and Alwasilah, 1996:127). Mind mapping with group working here is used as a main method to help the students to understand what the texts contain about. It can also help the students to improve their vocabulary mastery. If students can represent or manipulate a complex set of relationships in a diagram, they are more likely to understand those relationships, remember them, and be able to analyze their component parts (Davies, 2010:280). While group working is a small group that contains around 5 students that work together in learning process to get the aim of the lesson. It is possible to say that small group of around 5 students provoke greater involvement and participation than larger group. They are small enough for real interpersonal interaction, yet not so small that members are over-reliant upon each individual (Harmer, 2007:165). METHODOLOGY The researcher used descriptive qualitative in this study. McMillan (1992: 9) states that qualitative focuses on understanding meaning through verbal narratives and observations rather than through number. He writes simply to observe the process of teaching and learning in the classroom teaching and does not participate in the class. During the observation, the researcher described the activities in the classroom while using the method. The researcher also collected data in the form of field note, questionnaires, and student performance when applying this technique in the classroom. The participants of this study were the nine grade students of SMP Negeri 50 Surabaya. Nine grade students were chosen because in the process of collecting the data, the narrative text is being taught to them. Only a class with good record in English and considered by the teacher was chosen the participants of this research. According to the teacher, the most suitable participants of this research were 9-C. There are several questions in this research about mind mapping with group working as a method to teach reading narrative text such as how is the implementation of group working in teaching reading narrative text for nine grades of SMPN 50 Surabaya, how do the students response toward the implementation of group working in teaching reading narrative text?, how do the students response toward group working in reading narrative text. To answer the first question, the data was obtained by using observation checklist conformed by field note. Obviously, the data was presented in the form of sentences. To answer the second and third question, the data were obtained by using questionnaire. Since this was a descriptive qualitative research, the researcher used observation checklist, field notes, and questionnaire. Observation checklist consisted of list of questions in format “yes” or “no” to describe the situation in the classroom when the teacher implemented mind mapping method. The observation checklist contained some indicators, they are: the materials, teacher’s activities, students’ activities, and also group working as a reading method. The researcher here also used field note to support the data that has been collected by using observation checklist.. In this research, the researcher used unstructured field note for a free describing of the situation. In order to know students’ responses toward the implementation of group working and also the students’ responses toward group working, the researcher used questionnaire. Questionnaire consisted of questions related to the teaching materials and the topic of the text, teaching and learning process in the classroom, and the last was the students’ responses toward the implementation of group working and also group working. In this research, the researcher took part as an observer in the classroom. In collecting the data, the researcher did not take any part in teaching and learning process. First data, observation checklist and field note were collected through observing what was going on while the teacher was implementing group working to teach reading to nine grades. This is to observe and describe phenomenon during teaching and learning process. At the last meeting, the researcher presented the students questionnaire to find out students’ responses toward the implementation of group working and also group working in teaching narrative text. The data being analyzed were those come from observation check list, field notes, and questionnaire. Since this is a descriptive qualitative study, the data will be analyzed and described in the form of words or description. First, the researcher analyzed each of information in the observation through the results of observation checklist with the support of field note. The results of this method were analyzed and explained descriptively in the form of paragraph. The result was used to explain the implementation of group working in teaching reading narrative text. Second, to find out the students’ responses toward the implementation of group working in teaching reading narrative text and toward group working in reading narrative text, the researcher asked each student to give their responses in written form. RESULT AND DISCUSSION Result Based on the research that the researcher conducted, there were three meetings from this observation. The first observation was held on Monday, February 3rd 2014. At that time, the class began at 9.40 in the morning. The teacher asked the students about their prior knowledge on narrative text, especially fable. Only some of the students answered interest. The rest of the students answered not really interest. The teacher explained about the aim, the generic structure, and the language features of narrative text. After explaining about the types of narrative texts and their component, teacher also gave example of the text by distributing a paper that contains fable to the class. The teacher also wrote notes on the blackboard about the topic for the students to write it down in their book. After giving the example of narrative text, especially fable, teacher started to explain about mind mapping by using one of the examples text titled “Monkey and Crocodile”. Teacher asked the students prior knowledge about mind mapping and the branches system. Only one of the students named Syafik raised his hand and said “Peta Konsep”. After showing and presenting his explanation about mind mapping and the branches system into a text, teacher asked the students if there were any question about the explanation and also the example. No one raised their hands. Then teacher asked the students to open their book (Bahasa Inggris untuk SMP/MTs Intan Pariwara) page 88 and there was a text titled “Rat”. The teacher asked the students to make a group which contained 5-6 students. After the students finished grouping, then the teacher asked the students to use mind mapping and branches system to that text as shown in the example that has been given before based on what they remember about the text. Based on the students’ task that has been checked by the teacher in a glance and also their questions during teaching and learning process, the students did not really understand about mind mapping. Before the end of teaching and learning process, the teacher gave conclusions about the lesson that they had learned at that time. Then the teacher asked the students to do a follow-up assignment. After that, the teacher said goodbye and left the class. The second observation was held on Monday, February 10th 2014. On that day, the English class began at 09.40 am just like the usual time. teacher did brainstorming on the last assignment. The teacher discussed with the students about that last meeting assignment and the students responded enthusiastically. The teacher asked the students to open their book in the next page of their last assignment. The titled of the text at second meeting was “The Crow King”. Since this was the second meeting and the students had already known the implementation of mind mapping, the teacher did not guide them in details like in the first meeting. Based on the students’ task that had checked by the teacher in a glance, the students understanding about mind mapping are better than their understanding at the first day of observation. The third observation was held on Monday, February 17th 2014. At that time, the class began at 9.40 in the morning as usual. At this day, the researcher asked the students to write their responses toward the implementation of group working in teaching reading narrative text and also their responses toward group working in reading narrative text. The researcher asked the students to write on a paper individually about their responses toward the implementation of group working in teaching reading narrative text and also their responses toward group working in reading narrative text. The researcher also told the students to write their responses toward the materials that has been chosen by the teacher, the topic of the text, teaching and learning process in the classroom. To make the students more interested, after asking the students to finish their writing about group working, researcher presented a game for them. Researcher divided the students into 2 large groups; they were group A and B. The game was “Scrabble”. During this game, the students looked more interested rather than when the teacher was explaining about narrative text. At the end of the game, researcher gave a price to the group winner. To find out the students’ responses toward the implementation of group working in teaching reading narrative text, and also their responses toward group working in teaching reading, the researcher used unstructured questionnaire. After classifying the result of the questionnaire, the result was presented in the form of sentences. This is only one part of questionnaire. The researcher asked the students to write their responses individually and the responses must be different from one to another. The students were not allowed to see their friends’ answer. They must create the responses with their own words. The result of the questionnaire is that the students of IX-C class described the implementation of group working in teaching reading narrative text is really helpful. They described that their reading skill is better than before. Their knowledge about reading method is also increased since that was the first time they used group working in teaching reading narrative text. The students also described that by using group working in teaching reading really helps them to do the assignment with less difficulties rather than they do it individually just like their daily activities. Through group working, the learning activities become less bored and easier. The students also described about the teaching and learning materials that has been chosen by the teacher. The students said about the story that has been chosen by the teacher gave them more new vocabularies that they never had before. And also, the students said that the materials were not easy, but they felt it challenge them to be more active in reading class when they found something interesting in it. It shown from the student’s words on their questionnaire paper that submitted to the researcher. Some students stated that they like and felt more interested with this method and also they mentioned how useful this method in teaching and learning process. Also they mentioned about how hard the materials was. The result above is the main result of the whole class. Not every student gives positive answer, some of them also have their own responses toward the implementation of group working in teaching reading narrative text, and also their responses toward group working in teaching reading. Discussion Based on the result of the observation on the implementation of group working in teaching reading skill in narrative text for nine graders of SMP Negeri 50 Surabaya in the class, there were some results that could be discussed and explained further. During the observation on the students of SMP Negeri 50 Surabaya, the researcher found that the teacher’s implementation of group working method successfully to help the students to understand the text. It can be said successful based from the result of the observation checklist, field note and also the result of the questionnaire. The implementation of group working method in teaching reading narrative text (fable) makes reading activities become easier and meaningful because group working method made the students know the stages of reading and also this method helps the students to understand the text well. Besides that, the materials given by the teacher also help the students to build their vocabulary and their knowledge. In teaching reading, there are three stages that teacher can use to help the students understand more about reading. Pursuant to that, the teacher always divided the reading activities into three stages in every meeting. There are pre-reading stages, whilst-reading stages and also post-reading stages. In the first meeting, the students could not work cooperatively with the teacher during pre reading and whilst reading, because they talked among themselves so the students do not understand their teacher’s explanation about mind mapping with group working in learning reading narrative text (fable). In the second meeting, the students could work cooperatively with the teacher. They listen to the teacher’s explanation carefully during pre reading and whilst reading, so they can do their task better than before and also the method becomes more understandable for them. In the third meeting, the teacher gives a chance for the researcher to ask the students to write on a piece of paper about their responses towards group working individually whether in English or Bahasa. The major difficulty during teaching and learning activities was only they could not speak and understand English well. It is the vocabulary that stops the students from understanding the text. At the end of every meeting, except the third meeting, the teacher always asked the students to make a mind mapping of every text that has been chosen as the material of the lesson on that day. This task could be an indicator for the teacher whether the students understand about what are exactly mind mapping and how the group working method implements it into a text. Based on the result of questionnaires, the researcher found that group working could be applied in teaching reading narrative text to the ninth grade students in SMPN 50 Surabaya, especially students in the class of IX-C. The group working method helps them to do the assignment easier rather then they did it individually, and also they could easily understand what the text is about. As conclusion, group working were helped the students which can help them to build their reading ability and helped them in understanding the text. This method also could help the students to learn about exchange their ideas with another student. Moreover, the result which showed that the students reading ability was getting better can be seen from their task mistakes each meeting. Their motivation in reading using mind mapping with group working was high. CONCLUSION AND SUGGESTION Conclusion This study is conducted to know the implementation of group working in teaching reading skill in narrative text for nine graders, the students’ responses toward the implementation of group working, and also their responses toward group working. Based on the result of the data analysis which is obtained through observation checklist, field note, and also questionnaire, the researcher conclude that: group working can be applied as a method to teach reading narrative text because the students’ reading comprehension was getting better after the implementation of group working in reading activity it showed from the students’ task. Their motivation and interest helped them in comprehending every text. The students said group working helped them to understand the content of the materials. In addition, most of the students agreed that group working made the teaching and learning process become more entertaining and less boring. Suggestion After doing the research and getting the result, there are some suggestions from the implementation of group working in teaching reading narrative text for nine graders. The researcher would like to give some suggestions to English teachers especially one who has a concern to teach young learners. Some suggestions are also offered for future studies. For the teacher, it is a must to explain about mind mapping and group working clearly and understandable for the students. The students’ level of understanding the text of depends on how the teacher explains about this method. You must give the explanations of this method as simple as you can. A good, simple, and clear explanation led us to a good result of the implementation of group working. Then, a good comprehension of any text would likely follow. For the students, it is important to listen to every explanation from the teacher. Do not talk among your friends or doing something outside the teaching and learning activities. Group working is a simple, quiet understandable, and easy to apply method. But if you do not understand about its basic concept, you will not get the goal of this method and may you will get unsatisfying reading score at the end of teaching and learning process. DAFTAR PUSTAKA Azies, F and Chaedar, A. 2000. Pengajaran Bahasa Komunikatif Teori dan Praktek. Bandung: Remaja Rodakarya. Davies, M. 2010. Concept mapping, mind mapping, and argument mapping: What are the differences and do they matter?. Australia: Springer Science+Business Media. Harmer, J. 2001. The Practice of English Language Teaching Fourth Edition. England : Pearson Education Limited. Hirasawa, L and Linda Markstein. 1983. Developing Reading Skills (2nd Edition). London: New Burry House, Inc. Kustaryo, Sukirah. 1988. Reading Techniques for College Students. Jakarta: Departement Pendidikan dan Kebudayaan Direktorat Jenderal Pendidikan Tinggi Proyek Pengembangan Lembaga Pendidikan Tenaga Kependidikan. McMillan, J. H. 1997. Research in education: a conceptual introduction. Longman. Nunan, D. 2003. Practical English Language Teaching. UK: Prentice Hall International. Spalding, R. B and Spalding, W. T. 1990. Writing Road to Reading. English: HarperCollins Publishers.